Hyperfrakcionovaná akcelerovaná radioterapie s modulovanou intenzitou u pokročilých nádorů hlavy a krku - prediktivní faktory celkového přežití - Cvek, J; Knybel, L; Stránský, J; Matoušek, P; Res, O; Zeleník, K; Otáhal, B; Molenda, L; Skácelíková, E; Stieberová, N; Čermáková, Z; Feltl, D (Klinicka onkologie, 2017)
AIM: The aim of this study was to evaluate overall survival (OS) and prognostic factors in patients ineligible for chemotherapy who were treated with a hyperfractionated accelerated schedule with simultaneous integrated boost. MATERIAL AND METHODS: From May, 2008, to April, 2013, 122 patients with locally advanced nonmetastatic squamous laryngeal (14%), hypopharyngeal (30%), oropharyngeal (30%), and oral cavity (27%) cancer were treated at our institution. The median age, Karnofsky Performance Status (KPS), and gross tumor volume (GTV) of the patients were 63 years (range, 46-87 years), 80% (range, 50-100%), and 46 ml (range, 5-250 ml), resp. The median total dose of radiotherapy was 72.6 Gy (range, 62-77 Gy) at 1.4-1.5 Gy per fraction, and 55 Gy at 1.1 Gy per fraction was delivered for GTV (primary and lymphadenopathy) with a margin of 0.7 cm and regional lymphatic areas with a margin of 0.3 cm. The dose was delivered 2× a day, with a 6-8 hour interval between doses, via a 6 MeV linear accelerator. OS was estimated using the Kaplan-Meier method, and predictors of OS were analyzed using Cox proportional hazards regression. RESULTS: The median duration of the radiotherapy series was 37 days (range, 32-45 days). The incidence of grade 3 acute toxicity was 62% for mucosa (oral cavity and/or pharynx) and 0% for skin. Confluent mucositis cleared in all cases within 21 days. No grade 4 or 5 toxicities were recorded. PEG was introduced before treatment in 55 patients (45%). The 1-and 2-year OS was 65% and 32%, resp. KPS less than 80% (RR 2.4, 95% CI 1.3-4.2; p = 0.004), cancers other than oropharyngeal or laryngeal cancer (RR 2.0, 95% CI 1.1-3.5; p = 0.016), and capacity of high GTV (RR 1.006, 95% CI 1.001-1.011; p = 0.017) were found to be negative prognostic factors for OS. CONCLUSION: More than 30% of patients with poor prognosis survived for longer than 2 years. KPS before treatment was the strongest prognostic factor for better OS.Key words: head and neck cancer - radiotherapy dose fractionation - survival analysis - acceleration - hyperfractionation This work was supported by RVO-FNOs/2016 (HPV status as predictive and prognostic factor for primary and secondary head and neck cancer). The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 9. 3. 2017Accepted: 19. 4. 2017.
Keywords: Humans; lidé středního věku; radioterapie s modulovanou intenzitou; Aged; výsledek terapie; senioři; lidé; nádory hlavy a krku; Head and Neck Neoplasms; Kaplanův-Meierův odhad; Middle Aged; prognóza; Treatment Outcome; frakcionace dávky záření; Aged, 80 and over; senioři nad 80 let; Kaplan-Meier Estimate; Dose Fractionation, Radiation; Radiotherapy, Intensity-Modulated; Prognosis